2016
DOI: 10.1017/s0022226716000281
|View full text |Cite
|
Sign up to set email alerts
|

Effects of discourse on control

Abstract: This study examined discourse effects on obligatory and non-obligatory control interpretations. Seventy participants undertook three online forced-choice surveys, which monitored preferred interpretations in complement control, verbal gerund subject control, long-distance control and sentence-final temporal adjunct control. Survey 1 ascertained their baseline interpretations of the empty category in these constructions. Survey 2 primed the critical sentences used in survey 1 with a weakly established topic of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 23 publications
2
18
0
Order By: Relevance
“…More recently, Janke (2016) demonstrated that children aged between 6;9 and 11;3 do in fact permit object interpretations when that object is cued by a strongly established topic. The same result was found in a comparable study on 70 adults (Janke and Bailey, 2017). They did not, however, accept external-referent interpretations under the same amount of discourse pressure.…”
Section: Introductionsupporting
confidence: 89%
See 4 more Smart Citations
“…More recently, Janke (2016) demonstrated that children aged between 6;9 and 11;3 do in fact permit object interpretations when that object is cued by a strongly established topic. The same result was found in a comparable study on 70 adults (Janke and Bailey, 2017). They did not, however, accept external-referent interpretations under the same amount of discourse pressure.…”
Section: Introductionsupporting
confidence: 89%
“…However, there is another reason for this construction being an interesting topic to examine in children with autism, which relates to work that has revealed a lenience it exhibits in terms of the interpretations its ec permits. Recent experimental work on this sub-type of adjunct control has indicated that children's and adults' interpretations of the ec are not quite as previously assumed in the literature (see Janke, 2016, for children and Janke and Bailey, 2017, for adults). Using the aforementioned pragmatic lead paradigm, participants were asked to make referent-choice decisions in different sub-types of control which were preceded by no contextual cue, a weak contextual cue or a strong contextual cue.…”
Section: Introductionmentioning
confidence: 81%
See 3 more Smart Citations